2004
DOI: 10.1088/0953-4075/38/1/009
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the x-ray mass attenuation coefficient of silver using the x-ray-extended range technique

Abstract: We used the x-ray-extended range technique to measure the x-ray mass attenuation coefficients of silver in the 15-50 keV energy range with a level of uncertainty between 0.27% and 0.4% away from the K-edge. The imaginary part of the atomic form factor of silver was derived by subtracting the scattering component from the measured total mass attenuation coefficients. Discrepancies between the measured mass attenuation coefficients and alternative theoretical predictions are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
26
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 46 publications
(88 reference statements)
9
26
1
Order By: Relevance
“…Chantler (1995Chantler ( , 2000 studied the atomic form factors, photoelectric absorption, scattering crosssection and mass attenuation coefficients in the vicinity of absorption edges for the various element in the different energy regions. Other calculations of atomic form factors for measurement of attenuation coefficients are discussed elsewhere (Tran et al, 2003a(Tran et al, , 2003b(Tran et al, , 2005. Tran et al (2005) used the x-ray-extended range technique to measure the x-ray mass attenuation coefficients of silver in the 15-50 keV energy range with a level of uncertainty between 0.27% and 0.4% away from the K-edge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chantler (1995Chantler ( , 2000 studied the atomic form factors, photoelectric absorption, scattering crosssection and mass attenuation coefficients in the vicinity of absorption edges for the various element in the different energy regions. Other calculations of atomic form factors for measurement of attenuation coefficients are discussed elsewhere (Tran et al, 2003a(Tran et al, , 2003b(Tran et al, , 2005. Tran et al (2005) used the x-ray-extended range technique to measure the x-ray mass attenuation coefficients of silver in the 15-50 keV energy range with a level of uncertainty between 0.27% and 0.4% away from the K-edge.…”
Section: Introductionmentioning
confidence: 99%
“…Other calculations of atomic form factors for measurement of attenuation coefficients are discussed elsewhere (Tran et al, 2003a(Tran et al, , 2003b(Tran et al, , 2005. Tran et al (2005) used the x-ray-extended range technique to measure the x-ray mass attenuation coefficients of silver in the 15-50 keV energy range with a level of uncertainty between 0.27% and 0.4% away from the K-edge. A typical example of the method based on synchrotron radiation is the work of Chantler et al (2001) for the measurement of the X-ray mass attenuation coefficient of copper using 8.85-20 keV synchrotron radiation.…”
Section: Introductionmentioning
confidence: 99%
“…A recent and extensive set of synchrotron radiation measurements has appeared [20][21][22][23][24][25][26][27][28] in which the authors demonstrated painstaking effort to eliminate systematic errors identified in earlier measurements [15][16][17]. They examined attenuation coefficients for elements Si, Cu, Zn, Ag, Mo, Sn and Au with generally an overall five-fold improvement in measurement accuracy (typically to within 0.1-0.2%) with respect to earlier work.…”
Section: Previous Experimental Workmentioning
confidence: 99%
“…They examined attenuation coefficients for elements Si, Cu, Zn, Ag, Mo, Sn and Au with generally an overall five-fold improvement in measurement accuracy (typically to within 0.1-0.2%) with respect to earlier work. This has allowed, for the first time, a critical analysis of the available theories, generally extending from the K edge of each element and upward in energy; coefficients immediately below the K edge for Ag [23], Mo [24], Cu [25] and Zn [26] were also included. Another consideration made was to incorporate measurement energy spacings at close enough increments near the K edges to show fine structure detail.…”
Section: Previous Experimental Workmentioning
confidence: 99%
“…Chantler et al [13], Tran et al [14], and de Jonge et al [15] determined the imaginary form factors for Cu, Ag, and Sn, respectively, using the synchrotron radiation-based XERT technique. By using the gamma attenuation method, Appaji Gowda and Umesh [16] determined the anomalous scattering factors for Ta, Hg, and Pb around the K edge in the energy range 24-136 keV.…”
Section: Introductionmentioning
confidence: 99%